MINIMASI BIAYA SEWA PADA PENJADWALAN FLOWSHOP DENGAN MEMPERHATIKAN BREAKDOWN-TIME - Muhammad Faudzi Bahari; Ade Ima Afifa Himayati (JURNAL ILMU KOMPUTER DAN MATEMATIKA, 2024)
This research discusses a method for minimizing rental costs in flowshop scheduling. The method used is Nawaz, Enscor, and Ham (NEH) with three machines at the CV sandal company. SAMHARI. The company produces 6 different types of sandals. Several assumptions are used to support this research. The method used is expected to reduce the costs that the company must incur for each production. In the production process it is assumed that a breakdown occurs at 250-260 hours due to maintenance that must be carried out on the rented machine. The type of rental used is one order, so a method is needed that can minimize total production time so that production costs can be reduced to as low as possible. When the simulation is carried out, it can be seen that there is a difference in production costs of Rp. 251,774.